Buster makes the grade - Krensky, Stephen (Boston : Little, Brown and Company, 1999)
Arthur and his friends help Buster study for an important test so that he will be able to move on to the fourth grade with them.
Keywords: Schools -- Fiction; Rabbits -- Fiction; Aardvark -- Fiction; Animals -- Fiction